2021
DOI: 10.1111/faf.12594
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry across international borders: Research, fishery and management trends and economic value of the giant sea bass (Stereolepis gigas)

Abstract: Co-operation in the management of shared fish stocks is often necessary to achieve sustainability and reduce uncertainty. The United States of America (USA) and Mexico share a number of fish stocks and marine ecosystems, while there is some binational co-operation in scientific research, unilateral management decisions are generally the rule. We present a case study using the giant sea bass (Stereolepis gigas, Polyprionidae) to highlight how these management and research asymmetries can skew national perceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 113 publications
0
8
0
Order By: Relevance
“…All the deep-sea fishes had otolith chemistry significantly different from the giant sea 615 bass, Stereolepis gigas. The giant sea bass occurs within relatively shallow waters up to ~ 30 616 deep (Ramírez-Valdez et al, 2021). At this depth, oxygen and pH conditions vary, but values are 617 consistently higher than those found for our deep OMZ fishes (Table 1).…”
mentioning
confidence: 52%
“…All the deep-sea fishes had otolith chemistry significantly different from the giant sea 615 bass, Stereolepis gigas. The giant sea bass occurs within relatively shallow waters up to ~ 30 616 deep (Ramírez-Valdez et al, 2021). At this depth, oxygen and pH conditions vary, but values are 617 consistently higher than those found for our deep OMZ fishes (Table 1).…”
mentioning
confidence: 52%
“…One study that looked at the impact of Macrocystis pyrifera deforestation caused by urchin grazing on kelp forest food web structure found that the negative impacts of deforestation were not as strong at higher trophic levels similar to those occupied by giant sea bass (Graham 2004). Furthermore, a portion of the geographic range of giant sea bass does not coincide with the range of kelp (Ramírez-Valdez et al 2021), and there are anecdotal reports of the local extirpation of kelp from rocky reefs in the Channel Islands having no apparent influence on their presence (Domeier 2001). These findings suggest that threats to kelp forests do not necessarily equate to threats to giant sea bass.…”
Section: Discussionmentioning
confidence: 99%
“…Sampling took place from 2017 to 2020, and spanned the core range of giant sea bass, which is south of Pt. Conception, California, along the Pacific coast of Baja California and the upper Gulf of California, Mexico (Domeier 2001, Ramírez-Valdez et al 2021) (Fig. 1).…”
Section: Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…As oceanic conditions ( i.e ., sea surface temperature, productivity) change, aggregation cues may cause shifts in the timing and location of these aggregation events. Although recent genetic analyses have shown fish in Mexican waters may have helped US populations recover (Chabot et al ., 2015 ; Gaffney et al ., 2007 ; Ramírez‐Valdez et al ., 2021 ), there is no evidence to date documenting movement of fish between Mexico and the US. Currently, the only confirmed aggregation sites in U.S. waters are around Anacapa Island (Domeier, 2005 ), Santa Catalina Island (Clevenstine & Lowe, 2021 ; House et al ., 2016 ) and La Jolla, California (Blincow, unpubl.…”
mentioning
confidence: 99%